Mutations in the Gabrb1 gene promote alcohol consumption through increased tonic inhibition (2024)
ABSTRACT: Alcohol dependence is a common, complex and debilitating disorder with genetic and environmental influences. Here we show that alcohol consumption increases following mutations to the g-aminobutyric acidA receptor (GABAAR) b1 subunit gene (Gabrb1). Using N-ethyl-N-nitrosourea mutagenesis on an alcohol-averse background (F1 BALB/cAnN x C3H/ HeH), we develop a mouse model exhibiting strong heritable preference for ethanol resulting from a dominant mutation (L285R) in Gabrb1. The mutation causes spontaneous GABA ion channel opening and increases GABA sensitivity of recombinant GABAARs, coupled to increased tonic currents in the nucleus accumbens, a region long-associated with alcohol reward. Mutant mice work harder to obtain ethanol, and are more sensitive to alcohol intoxication. Another spontaneous mutation (P228H) in Gabrb1 also causes high ethanol consumption accompanied by spontaneous GABA ion channel opening and increased accumbal tonic current. Our results provide a new and important link between GABAAR function and increased alcohol consumption that could underlie some forms of alcohol abuse.